Avaliação retrospectiva das alterações patológicas em cetáceos odontocetos no estado do Ceará (1993-2018) - Thomaz, Mayra Csapo (2024)
Studies focused on pathological alterations are fundamental for understanding the causes of stranding and death of cetaceans. Thus, the objective was to describe the main necropsy findings in stranded odontocete cetaceans on the beaches in the state of Ceará, Brazil, between the years 1993 and 2018, suggesting possible stranding causes. Thirty-eight axial skeletons and necropsy reports of odontocete cetaceans were investigated, represented by seven species: Sotalia guianensis (n=14), Stenella clymene (n=8), Stenella longirostris (n=5), Stenella frontalis (n=4), Peponocephala electra (n=3), Globicephala macrorhynchus (n=3), and Stenella coeruleoalba (n=1). The lesions were grouped into categories and named as inflammatory, degenerative, traumatic, developmental/malformation, parasitic, infectious, vascular, anthropic, post-mortem, and miscellaneous processes. Strandings and their respective alterations were analyzed according to the stranding region. The results revealed a variety of lesions, where in a single animal it was possible to find more than one lesion of diverse origins. Alterations were observed in approximately 95% of the animals, with a predominance of parasitic alterations (27.1%), mainly represented by the presence of cestodes and nematodes in various organs. Inflammatory lesions were observed in 22.2% of the animals, many secondary to underlying causes. Developmental lesions accounted for 16.8% of the alterations and were mostly characterized by the non-closure of the neural arch in cervical vertebrae. Traumatic lesions were found in 15% of the animals and were more common in the ribs, followed by lumbar vertebral processes. Lesions of infectious and vascular origin accounted for 6.6% and 3% of the observed lesions, respectively. The Metropolitan Region of Fortaleza shows a concentration in the number of strandings, raising hypotheses about how urbanization can be a multifactorial cause of cetacean strandings. These results contribute to the basic understanding of diseases affecting stranded cetaceans in Brazil and may be valuable for comparative pathology purposes and analysis of environmental influence on cetacean populations, as these findings may have origins in environmental variations, resulting in the cause of death or stranding of these animals.